Impaired lung function and mortality risk in men and women: findings from the Renfrew and Paisley prospective population study. - Hole, D. J. (BMJ Group, 1996)
OBJECTIVE: To assess the relation between forced expiratory volume in one second (FEV1) and subsequent mortality. DESIGN: Prospective general population study. SETTING: Renfrew and Paisley, Scotland. SUBJECTS: 7058 men and 8353 women aged 45-64 years at baseline screening in 1972-6. MAIN OUTCOME MEASURE: Mortality from all causes, ischaemic heart disease, cancer, hung and other cancers, stroke, respiratory disease, and other causes of death after 15 years of follow up. RESULTS: 2545 men and 1894 women died during the follow up period. Significant trends of increasing risk with diminishing FEV1 are apparent for both sexes for all the causes of death examined after adjustment for age, cigarette smoking, diastolic blood pressure, cholesterol concentration, body mass index, and social class. The relative hazard ratios for all cause mortality for subjects in the lowest fifth of the FEV1 distribution were 1.92 (95% confidence interval 1.68 to 2.20) for men and 1.89 (1.63 to 2.20) for women. Corresponding relative hazard ratios were 1.56 (1.26 to 1.92) and 1.88 (1.44 to 2.47) for ischaemic heart disease, 2.53 (1.69 to 3.79) and 4.37 (1.84 to 10.42) for lung cancer, and 1.66 (1.07 to 2.59) and 1.65 (1.09 to 2.49) for stroke. Reduced FEV1 was also associated with an increased risk for each cause of death examined except cancer for lifelong nonsmokers. CONCLUSIONS: Impaired lung function is a major clinical indicator of mortality risk in men and women for a wide range of diseases. The use of FEV1 as part of any health assessment of middle aged patients should be considered. Smokers with reduced FEV1 should form a priority group for targeted advice to stop smoking.